Analysis of the use of learning models in physics subjects at SMAN 9 Kota Tangerang Selatan Banten - Indri Sari Utami; Ruth Soukaning Nugrah Djati; Yus Rama Denny; Yuvita Oktarisa (Universitas Sultan Ageng Tirtayasa, 2020)
The learning model is a frame in a learning process that can support the achievement of learning objectives. This study aims to determine, 1) the learning model used in physics subjects in schools, 2) the obstacles faced by the teacher in applying the learning model, and 3) efforts to overcome the obstacles in applying the learning model to achieve learning objectives. This research method is qualitative research. The survey was conducted on one physics teacher and three students determined by random sampling—observation data collection using interviews and documentation systems. While the data analysis technique used is descriptive qualitative analysis technique. From the research results obtained that: 1) the learning model carried out in the learning process at SMAN 9 Kota Tangerang Selatan Banten is CL (Cooperative Learning) and CTL (Contextual Teaching and Learning), 2) the constraints faced by the teacher when implementing the learning model are the ability students who are lacking in understanding the concepts of physics so that the difficulty in solving problems and challenges in choosing the equations used, 3) efforts to overcome the obstacles in using learning models are needed to develop appropriate learning models such as STEM-based CTL models that make students construct their knowledge.